32nd International Vicenza Course on Hemodialysis and Peritoneal Dialysis, Vicenza, Italy, June 10-13, 2014 Abstracts - Yigit, I. P.; Celiker, H.; Dogukan, A.; Ilhan, N.; Guler, A.; Ulu, R.; Aygen, B. (Karger, 2014)
[Abstract Not Available]